Analysis of Flow Characteristics of Different Shape Particles Chasing. Issue 1 (1st February 2022) - Xu, Xiaodong; Zeng, Zhuoxiong; Guo, Kaifang
Abstract: in order to study the gas flow characteristics of particles with different shapes in the pursuit process, spherical, ellipsoidal and square particles are selected for numerical simulation by fluent. The results show that when the pursuit speed is the same, the streamline produced by square particles in the pursuit process is denser than that of spherical and ellipsoidal particles. Particle movement creates a certain vacuum on both sides and rear of the particle, causing the surrounding air flow to enter the areas on both sides of the particle, resulting in strong turbulence. After the rear particles catch up with the front particles, the changes of the surrounding flow field and streamline are similar to the inverse process before catching up, indicating that the particle motion has a certain regularity, and the square particles have the largest turbulent kinetic energy among the three particles.